The Case for Same-Sex Marriage Before the European Court of Human Rights. Issue 12 (15th October 2018) - Hamilton, Frances
ABSTRACT: For proponents of same-sex marriage, this essay sets forward a critical analysis of relevant arguments before the European Court of Human Rights. The privacy aspect of Article 8 European Convention of Human Rights will never be a successful argument with reference to marriage, which involves a public status. The equality argument (Article 14) is useful in addressing this issue with its close connections with citizenship, symbolic value, and proven record internationally. Difficulties remain with the equality argument; its conditional status, the width of the margin of appreciation allocated, and the need for an equality comparator. The equality argument needs reinforcement by use alongside a developing family law argument under Article 8 and a dynamically interpreted Article 12 (right to marry) argument. Ultimately, the success of any argument depends on convincingly influencing the European Court to consider that sufficient consensus has developed among Member States of the Council of Europe.